Polylactic acid (PLA) biocomposites filled with waste leather buff (WLB) - Ambone, Tushar; Joseph, Seena; Deenadayalan, E.; Mishra, Satyendra; Jaisankar, S.; Saravanan, P. (Journal of Polymers and the Environment, 2017)
A large amount of leather waste is generated from tanning industries and most of which are disposed of landfill or discharged into the natural water bodies without any treatment, causing environmental problems. The aim of this study is to develop eco-biocomposites using waste leather buff (WLB) as filler in Polylactic acid (PLA) matrix to reduce the environmental issues and provide sustainable solution. WLB/PLA composites were prepared by twins-screw micro extruder varying the WLB content from 2% to 30 wt%. These composite were extensively characterise by several techniques. Tensile properties of the composites showed addition of WLB resulted in improvement of tensile property of composite and reduction in percentage crystallinity of PLA matrix observed with increase in WLB content. The effect of WLB on properties of interfacial adhesion and dispersion in WLB/PLA composites were studied by SEM. Wettability of composites was tested by contact angle and water absorption studies. WLB/PLA composite showed increase in water absorption with WLB loading. These WLB/PLA composite could be used to develop low cost eco-friendly product material.

Fluorinated nanocellulose-reinforced all-organic flexible ferroelectric nanocomposites for energy generation - Ram, Farsa; Ambone, Tushar; Sharma, Aakash; Murugesan, Rajarathinam; Kajale, Deepak; Borkar, Vivek; Ali, Shaikh Faruque; Balu, Praveen Kumar; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Journal of Physical Chemistry C, 2018)
We report here enhanced ferroelectric crystal formation and energy generation properties of polyvinylidene fluoride (PVDF) in the presence of surface-modified crystalline nanocellulose. Incorporation of only 2-5 wt % fluorinated nanocellulose (FNC) in PVDF has been found to significantly induce polar beta/gamma-phase crystallization as compared to the addition of unmodified nanocellulose (carboxylated nanocellulose). A device made up of electrically poled PVDF/FNC composite films yielded 2 orders of magnitude higher voltage output than neat PVDF in vibrational energy harvesting. This remarkable increase in energy generation properties of PVDF at such a low loading of an organic natural biopolymer could be attributed to the tailored surface chemistry of nanocellulose, facilitating strong interfacial interactions between PVDF and FNC. Interestingly, energy harvesting devices fabricated from PVDF/FNC nanocomposites charged a 4.7 mu F capacitor at significantly faster rate and the accumulated voltage on capacitor was 3.8 times greater than neat PVDF. The fact that PVDF/FNC nanocomposites still retain a strain at break of 10-15% and can charge a capacitor in few seconds suggests potential use of these nanocomposites as flexible energy harvesting materials at large strain conditions.

Highly flexible mechanical energy harvester based on nylon 11 ferroelectric nanocomposites - Ram, Farsa; Radhakrishnan, Sithara; Ambone, Tushar; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2019)
We report here a flexible piezoelectric energy harvester using castor-oil-derived nylon 11 and biomass-derived cellulose nanocrystals (CNC). Using a simple solution casting process, we were able to fabricate flexible large area nylon 11 and composite films. Neat nylon 11 films crystallized predominantly in the α- phase. Incorporation of CNC at a low concentration of 2–5 wt % resulted in almost complete transition of α-phase to polar γ-phase, which could be attributed to strong hydrogen bonding interactions between CNC and amide groups in nylon 11. This remarkable shift in crystallization behavior also led to enhanced piezoelectric performance. We also found that the addition of 5 wt % glycerol (on the dry weight of nylon 11 or composite) enhanced the flexibility of the film. Energy harvesting devices made from 5 wt % nylon 11/CNC films showed about 2.6 times higher output voltage as compared to neat nylon 11 devices under similar impact conditions, and the effect was durable over 800 cycles. These devices were also used to charge a 10 μF polarized capacitor, and we found that the 5 wt % nylon 11/CNC devices charged up to 3.78 V in 90 s, which is 2.8 times higher than nylon 11 devices. To the best of our knowledge, this is the first report on nylon 11 nanocomposites, where cellulose nanocrystals have been used to enhance the electroactive γ phase in nylon 11 and yield such high piezoelectric performance.

Enhancing the mechanical properties of 3D printed polylactic acid using nanocellulose - Ambone, Tushar; Torris, Arun; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2020)
We report here a systematic investigation of the mechanical properties of polylactic acid (PLA) processed by fused filament fabrication (FFF) 3D printing vs PLA processed by compression molding. Our results show that the tensile strength and modulus of FFF-PLA is 49% and 41% lower, respectively, than compression molded samples of PLA. We also demonstrate here an approach to augment the mechanical properties of 3D printed PLA using nanocellulose. Incorporation of a small quantity (1 wt%) of cellulose nanofibers (CNF) was found to enhance the tensile strength and modulus of 3D printed PLA by 84% and 63%, respectively. X-ray microtomography was used to probe the morphology of 3D printed PLA and PLA/CNF composites. 3D printed PLA/CNF composites had significantly lesser voids as compared to neat 3D printed PLA. Differential scanning calorimetry study revealed that CNF can accelerate the nucleation and crystallization of 3D printed PLA leading to enhanced crystallinity. The thermal stability of 3D printed PLA/CNF composites was not compromised by the addition of CNF. The enhanced mechanical properties of 3D printed PLA/CNF composites can be ascribed to higher crystallinity and lesser defects.
Keywords: 3D printing; Biocomposites; composites; fused filament fabrication (FFF); Nanocellulose; polylactic acid (PLA)